2018
DOI: 10.1016/j.jfda.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle biosynthesis by using phenolic acids in rice husk extract as reducing agents and dispersants

Abstract: Rice husk extract, obtained using acid and alkali pretreatment extraction (AAPE), contains bioactive compounds and exhibits reducing abilities. Phenolic composition in rice husk extract was analyzed and the mechanism of silver nanoparticle (AgNP) biosynthesis by using AAPE rice husk extract was investigated in this study. Stable and spherically shaped AgNPs with a size of <15 nm were prepared under the following conditions: 0.001 M AgNO, AAPE rice husk extract diluted 10 times, pH 10, and reacted at 25 °C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 26 publications
6
49
0
Order By: Relevance
“…The synthesized particles exhibited maximum absorption at 407 nm, which represents the characteristic peak for AgNPs ( Figure 2 A). In line with these findings, several studies have demonstrated that flavonoids and phenolic compounds, such as quercetin and caffeic acid, can reduce Ag + quickly, and can act effectively as both reducing and stabilizing agents [ 23 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The synthesized particles exhibited maximum absorption at 407 nm, which represents the characteristic peak for AgNPs ( Figure 2 A). In line with these findings, several studies have demonstrated that flavonoids and phenolic compounds, such as quercetin and caffeic acid, can reduce Ag + quickly, and can act effectively as both reducing and stabilizing agents [ 23 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 80%
“…The FTIR spectrum showed absorption bands at 3422, 2922, 1742, and 1042 cm −1 , indicating the presence of a capping agent within the nanoparticles ( Figure 2 C). The band at 3422 cm −1 in the spectrum corresponds to the O–H stretching vibration indicating the presence of alcohol and phenol [ 28 ]. Bands at the 2922 cm −1 region were observed, arising from C–H stretching of aromatic compound.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be said that OPL extract has good chelating potency due to the presence of higher amount of TPC. Various phenolic compounds including caffeic, ferulic, protocatechuic acids, and gallic acid with hydroxyl and carboxylic groups have been reported to be responsible for conversion of metallic ions into metal particles . Phenolic compounds containing O─H groups are reported to be oxidized during reduction of gold ions into biocompounds with carbonyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic acids are characterized by the presence, in their molecular structure, of a carboxylic acid group and one or more hydroxyl groups, which confer antioxidant activity to them [28]. It is generally agreed that both the hydroxyl and the carboxylic acid groups are involved in the formation of nanoparticles [29][30][31]. In particular, the hydroxyl groups are responsible for the reduction of metal ions to the zero-valent metal, while the carboxyl groups act as stabilizing agents.…”
Section: Discussionmentioning
confidence: 99%